Kinetics of two redox reactions in 2‐butoxyethanol and water near its critical point of solution. Issue 4 (24th January 2019) - Du, Zhongyu; Duan, Siyu; Ma, Mingfang; Xu, Xiangyu; Li, Zhenquan; Kong, Lingdong; Liu, Jun
Abstract: The rate constants of two redox reactions Fe ( CN ) 6 4 − + S 2 O 8 2 − and Fe ( phen ) 3 2 + + S 2 O 8 2 − in the critical solution of 2‐butoxyethanol and water have been measured by using the UV spectrophotometry at the initial reaction stage. It was found that the rate constants at various temperatures for two reactions were well described by the Arrhenius equation in the noncritical region. The critical slowing down effect was detected in the critical region. The critical slowing down exponents were determined to be 0.044 ± 0.004 and 0.046 ± 0.005 for reactions Fe ( CN ) 6 4 − + S 2 O 8 2 − and Fe ( phen ) 3 2 + + S 2 O 8 2 −, respectively. The values of the critical slowing down exponents showed that only dynamic critical slowing down effect, and no thermodynamic singularity could be observed for the two reactions.